Musical Accompaniment of Wayang Sukuraga - Sundawati, Kinanti Putri (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2023)
Wayang Sukuraga is a puppet performance accompanied by musical accompaniment. Music accompaniment is one of the main components of the show. This study discusses the various types of musical accompaniment used in wayang sukuraga performances. The purpose of this study is to describe the uniqueness of the musical accompaniment used in the Sukuraga puppet show, which is different from other puppet shows. The method used in this study is a descriptive qualitative method to examine the musical accompaniment in the Wayang Sukuraga performance. Literacy studies from various relevant literature and interviews with the creators of Wayang Sukuraga. The results of this study include two musical accompaniments in Wayang Sukuraga, namely vocal sounds originating from the puppeteer in the form of songs for each Wayang Sukuraga character and traditional accompaniment music, namely gamelan.